IMPLEMENTASI PROGRAM MAKANAN BERGIZI GRATIS (MBG) SEBAGAI UPAYA PENINGKATAN PENGETAHUAN GIZI DAN PERILAKU MAKAN SEHAT SISWA SEKOLAH DASAR NEGERI 011 SEKUPANG BATAM - amalia, eva; Afriani, Miratia; Arif Gunawan, Agung (Jurnal Tiyasadarma, 2026)
Optimal nutrition plays an essential role in supporting the growth and learning process of elementary school students. The Free Nutritious Meal Program (MBG) is a strategic government initiative that requires support through nutrition education and the development of healthy eating habits at school. This community service program aimed to improve students’ nutritional knowledge and promote healthy eating behavior among students at SD Negeri 011 Sekupang through nutrition education integrated with the implementation of MBG. The methods included coordination with the school, interactive nutrition education sessions, meal-time assistance, and observation of menus and students’ eating behavior. The results showed an improvement in students’ understanding of the importance of balanced nutrition and increased awareness of healthy eating practices. In addition, the program strengthened the role of teachers and schools in supporting the sustainability of school-based nutrition programs. Integrated nutrition education within the MBG program contributes positively to the formation of healthy eating habits among elementary school students.